Florida Solid and Hazardous Waste Regulation Handbook: Private Regulation - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
Another form of solid and hazardous waste regulation is through private lawsuits. These lawsuits may be based on the legal principles of: nuisance, trespass (both intentional and unintentional), negligence, and  strict liability. This is EDIS document FE465, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.